Diffuse alveolar hemorrhage during alemtuzumab infusion in a patient with multiple sclerosis: a case report - Aija Zuleron Myro; Gisle Bjerke; Svetozar Zarnovicky; Trygve Holmøy (BMC, 2018)
Abstract Background Diffuse alveolar bleeding is a potentially life-threatening condition that can be induced by several drugs. Whereas fatal cases have been reported in patients treated for other indications, no report have so far been published in a patient with multiple sclerosis treated with alemtuzumab. Case presentation We report a case of alemtuzumab-induced diffuse alveolar bleeding in a 29 year old woman with relapsing remitting multiple sclerosis. The patient developed acute shortness of breath, chest pain on inspiration and haemoptysis following the second infusion of alemtuzumab during the first treatment cycle. Computed tomography showed bilateral alveolar opacities. Bronchoscopy and broncho-alveolar lavage showed persistently bloody return with no evidence of infection. The symptoms resolved completely without treatment and control computed tomography performed one week later showed total resolution of pulmonary infiltrates. Conclusion This is the first published report of diffuse alveolar bleeding in a patient with multiple sclerosis treated with alemtuzumab. Four similar cases in patients treated for multiple sclerosis and several fatal cases in patients treated for other conditions are registered at the World Health Organization database of suspected adverse events (VIgiBase©), underscoring that this is a serious and possibly under-recognized complication of alemtuzumab which can also occur in the treatment of multiple sclerosis. The clinician should consider the possibility of diffuse pulmonary haemorrhage in patients with sudden onset of respiratory distress and haemoptysis following administration of alemtuzumab for multiple sclerosis.